Characteristic of cerebral hemodynamics and functional connectivity in patients with neuropathic pain after spinal cord injury: an exploratory study - Yu, Yang; Ma, Yuqin; Cheng, Meiling; Huang, Zebin; Lei, Honghui; Su, Sitong; Huang, Fubiao; Wang, Fangyong (Frontiers in Neuroscience, 2025)
BackgroundThis study investigated the brain functional characteristics of patients with neuropathic pain (NP) following spinal cord injury (SCI) using functional near-infrared spectroscopy (fNIRS).MethodsA total of 35 subjects were enrolled, including 10 able-bodied controls, 12 patients with SCI and NP (SCI-NP), and 13 patients with SCI (without NP). fNIRS was used to detected blood oxygen signals during motor tasks and resting-state (RS) functional connectivity (FC) in the subjects. We also performed Pearson correlation analyses of pain scores (NPS) and the Pittsburgh Sleep Quality Index (PSQI) in patients with SCI-NP. Statistical analyses were performed using Shapiro-Wilk test for normality; paired t-test for intra-group differences; ANOVA (LSD post-hoc, Bonferroni-corrected) for multi-group comparisons; Cohen's d/partial η2 for effect size; independent samples t-test (FDR-corrected) for inter-group FC differences.ResultsDuring the task state, patients with SCI-NP activated bilateral primary somatosensory cortex (S1, L/R P = 0.044/0.032), bilateral supplementary motor area (SMA, L/R P = 0.041/0.037), right primary motor cortex and left parietal lobe (LPL, P = 0.047). Hemodynamic changes in the bilateral S1, secondary somatosensory cortex, SMA, and right prefrontal cortex of patients with SCI-NP were significantly stronger than those in the other two groups. During RS, the whole-brain and most inter/intra-regional FC strength trended able-bodied controls > patients with SCI > patients with SCI-NP. NPS strongly correlated with LPL (r = 0.977, P = 0.004); PSQI correlated with motor cortex HbO changes (r = 0.889−0.975, P = 0.005−0.043).ConclusionPatients with SCI-NP exhibit significant abnormal cerebral cortical excitation and reduced FC. HbO is a potential biomarker for evaluating NP. fNIRS supports objective assessment of SCI-NP and rehabilitation strategy formulation [ChiCTR2500097098].